The Puritan Ownership of a Cistercian Missal from Kirkstall Abbey. (5th December 2018) - Wilde, Philip
Abstract: This paper discusses a previously unknown printed Cistercian missal held at the Leeds Central Public Library. The article endeavours to demonstrate how the preservation of the book over a period of some two hundred and fifty years following the Dissolution was due to protestant families in the Leeds area. Further evidence confirms that it was puritans who were responsible for its initial preservation. It also aims to show that annotations to the kalendar and text establish that the book was in use in a pre-Dissolution religious house in the North of England. Evidence of provenance will suggest that this house is most likely to have been Kirkstall abbey near Leeds in Yorkshire.